Medicalisation, pharmaceuticalisation, or both? Exploring the medical management of sleeplessness as insomnia - Coveney, Catherine (Sociol Health Illn, 2018)
In this paper we examine the medical management of sleeplessness as ‘insomnia’, through the eyes of general practitioners (GPs) and sleep experts in Britain. Three key themes were evident in the data. These related to (i) institutional issues around advocacy and training in sleep medicine (ii) conceptual issues in the diagnosis of insomnia (iii) and how these played out in terms of treatment issues. As a result, the bulk of medical management occurred at the primary rather than secondary care level. These issues are then reflected on in terms of the light they shed on relations between the medicalisation and the pharmaceuticalisation of sleeplessness as insomnia. Sleeplessness, we suggest, is only partially and problematically medicalised as insomnia to date at the conceptual, institutional and interactional levels owing to the foregoing factors. Much of this moreover, on closer inspection, is arguably better captured through recourse to pharmaceuticalisation, including countervailing moves and downward regulatory pressures which suggest a possible degree of depharmaceuticalisation in future, at least as far prescription hypnotics are concerned. Pharmaceuticalisation therefore, we conclude, has distinct analytical value in directing our attention, in this particular case, to important dynamics occurring within if not beyond the medicalisation of sleeplessness as insomnia.